Optimization of Process Flow Diagrams for Processing of Mineral Wastes - Bardovsky, A. D.; Gorbatyuk, S. M.; Albul, S. V.; Gorbatyuk, N. V. (Metallurgist (New York), 2021)
This paper describes an algorithm for optimizing process flow diagrams, as well as the order in which the parameters of mineral waste recycling equipment should be optimized. We developed a flow chart for this waste-recycling process-train design analysis algorithm. When comparing different mineral-waste recycling process train options, it is best to use an generalized specific action criterion based on the total power consumption of the machinery, the total weight of equipment, and the average cycle time per unit volume (or weight) of recycled end product. We have developed an engineering technique for evaluating equipment systems, which enables selection of the most efficient mineral waste recycling equipment for production of end products of a given quality under certain specific production conditions, subject to the constraint that unit cost be minimized. A sample comparison is made to determine the efficiency of various types of equipment when producing finely-ground limestone from recycled limestone waste.